Do Hospital Characteristics Influence Cancer-Specific Survival for Early Stage Lung Cancer? - David, Elizabeth A (Am J Surg, 2015)
BACKGROUND: Quality of oncologic outcomes is of paramount importance in the care of patients with non-small cell lung cancer (NSCLC). We sought to evaluate the relationship of hospital volume for lobectomy on cancer-specific survival in NSCLC patients treated in California, as well as the influence of Committee on Cancer (CoC) accreditation. METHODS: The California Cancer Registry was queried from 2004–2011 for cases of Stage I NSCLC and 8,345 patients were identified. Statistical analysis was used to determine prognostic factors for cancer-specific survival. RESULTS: 7,587 patients were treated surgically. CoC accreditation was not significant for cancer-specific survival, but treatment in high volume centers was associated with longer survival when compared to low and medium volume centers (HR 1.77, 1.474–2.141 and HR 1.23, 1.058–1.438). CONCLUSIONS: These data suggest that surgical treatment in high volume hospitals is associated with longer cancer-specific survival for early-stage NSCLC, but that CoC accreditation is not.